2020
DOI: 10.1136/jech-2020-214058
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in suicide in Taiwan over a century: a time trend analysis in 1905–1940 and 1959–2012

Abstract: BackgroundSuicide rates are higher in men than in women in most countries, although the gender ratios vary markedly worldwide. We investigated long-term trends in suicide rates and the male-to-female ratios in relation to age, method and economic factors in Taiwan during the Japanese colonial (1905–1940) and postwar (1959–2012) periods.MethodsSuicide data were from the Statistical Reports of Taiwan Governor’s Office (1905–1940), Vital Statistics (1959–1970) and cause-of-death mortality data files (1971–2012). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Some of these studies also found that financial crises, periods of recession, and unemployment have a higher impact in specific subgroups, especially among the youngest and among men 31 . Probably, these groups are more affected by economic crisis.…”
Section: Discussionmentioning
confidence: 96%
“…Some of these studies also found that financial crises, periods of recession, and unemployment have a higher impact in specific subgroups, especially among the youngest and among men 31 . Probably, these groups are more affected by economic crisis.…”
Section: Discussionmentioning
confidence: 96%
“…Another cluster is dedicated to understanding the effects of marketization and medicalization on the public health sector. For example, Chang (2009)‘s study finds that the disengagement of the earlier public health stations with the local community is the result of the marketization and over-medicalization of the public health sector. Over-medicalization disproportionately increases doctors’ social status, but at the same time weakens other health professions’ status (Chang, 2003).…”
Section: Searching For Autonomy and Alternative Discourses: The Phl M...mentioning
confidence: 99%